2021
DOI: 10.1111/acer.14591
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Motives and Drinking Consequences across Days: Differences and Similarities between Moderate, Binge, and High‐Intensity Drinking

Abstract: Background The current study examined the extent to which within‐person variation in drinking motives differentiates moderate, binge, and high‐intensity drinking; and independent associations of motives and drinking intensity with alcohol use consequences in a sample of young adult drinkers from across the United States. Methods Participants were past 30‐day drinkers in the U.S. nationally representative Monitoring the Future 12th grade sample in 2018, who also reported alcohol use during a 14‐day data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…Data suggest event-specific drinking motives and protective behavioral strategies are associated with event-specific HID, as well as the risk of specific negative outcomes. For example, on a given drinking day, reporting stronger enhancement and social drinking motives was associated with higher drinking intensity, and stronger enhancement and coping motives were associated with more negative consequences (Patrick & Terry-McElrath, 2021). Further, Linden-Carmichael et al (2019) found using manner of drinking strategies weakened associations between HID and passing out from drinking, and using serious harm reduction strategies weakened associations between HID and having no one sober enough to drive and experiencing regretted sexual behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data suggest event-specific drinking motives and protective behavioral strategies are associated with event-specific HID, as well as the risk of specific negative outcomes. For example, on a given drinking day, reporting stronger enhancement and social drinking motives was associated with higher drinking intensity, and stronger enhancement and coping motives were associated with more negative consequences (Patrick & Terry-McElrath, 2021). Further, Linden-Carmichael et al (2019) found using manner of drinking strategies weakened associations between HID and passing out from drinking, and using serious harm reduction strategies weakened associations between HID and having no one sober enough to drive and experiencing regretted sexual behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The Young Adult Daily Life (YADL) Study is a longitudinal follow-up of a subsample of MTF participants who reported past 30-day alcohol use in 12th grade (Patrick & Terry-McElrath, 2021). YADL is designed to examine predictors and consequences of binge and HID (Patrick & Terry-McElrath, 2021). Although YADL is ongoing, the present study presents information from participants' initial YADL survey, completed in 2019, 1 year after the 12th-grade MTF survey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have found that up to 45% of young adults who binge drink also engage in high-intensity drinking (HID), or episodes during which females consume 8 or more drinks and males consume 10 or more drinks (Patrick, Terry-McElrath, et al, 2016), and that this level of consumption also peaks in young adulthood (Patrick & Terry-McElrath, 2019; Patrick et al, 2017). High-intensity drinkers also engage in binge drinking almost twice as frequently as non-high-intensity drinkers (Patrick, Terry-McElrath, et al, 2016), and there is evidence that HID incurs additional negative consequences above that associated with binge drinking (Patrick & Terry-McElrath, 2021; White et al, 2016). Although it was initially thought that HID characterized a specific subset of young adult drinkers, past studies have found that the tendency to engage in HID varies more within person than it does between people (Patrick, Cronce, et al, 2016; Patrick & Terry-McElrath, 2021).…”
Section: The Present Studymentioning
confidence: 99%
“…In contrast, enhancement and coping motives for alcohol use exhibit a more complex relationship with drinking and related problems. For instance, some studies have found that young adults drinking to enhance or to cope tend to drink more heavily and experience more harms such as blackouts or developing symptoms of alcohol use disorders (Cooper, 1994;Cooper et al, 2000;Patterson et al, 2020;Simons et al, 2000), while other studies show that coping motives are not related to heavier drinking (Cook et al, 2020;Patrick & Terry-McElrath, 2021;Skalisky et al, 2019;Stevenson et al, 2019).…”
Section: Alcohol and Cannabis Use Motivesmentioning
confidence: 99%